Analysis of Perceptions of the Bajo Community on the Construction of the Kendari-Toronipa Tourism Road in Bajo Indah Village and Leppe Village, Konawe Regency - Syahrun syahrun; Alias alias; M. Hafiz Sukri Sukri; Mursin mursin; Sitti Nilawati Samad; Nurmia Alimudin (Universitas Halu Oleo, 2023)
Abstract: This study aims to analyze the perception of the Bajo people towards the construction of the Kendari -Toronipa tourist road in Bajo Indah and Leppe Village, Konawe Regency. The research method used is a qualitative approach with data collection through in-depth interviews and participatory observation. The results showed that the Bajo community has a complex view of the development. Although they see the potential economic benefits offered by the construction of tourist roads, they also have concerns about the possible social, cultural, and environmental impacts. In this context, the adoption of a balanced approach between development and cultural preservation is important. This research provides insight into the dynamics of community views in dealing with local development, as well as underlining the need to involve communities in sustainable development decision-making. This finding has important implications for development planning that takes into account cultural, social, and environmental aspects in coastal areas. Keywords: Perception, Bajo Society, Development, Tourism